Abiraterone acetate plus prednisone in non-metastatic biochemically recurrent castration-naïve prostate cancer. (November 2021) - Spetsieris, Nicholas; Boukovala, Myrto; Alafis, Ioannis; Davis, John; Zurita, Amado; Wang, Xuemei; Tu, Shi-Ming; Chapin, Brian F.; Aparicio, Ana; Corn, Paul; Wang, Jennifer; Subudhi, Sumit K.; et al.
Abstract: Background: Intermittent androgen deprivation therapy (ADT) in biochemically recurrent castration-naïve prostate cancer is non-inferior to continuous therapy. We hypothesised that finite-duration abiraterone acetate plus prednisone (Abi +P) added to ADT will further reduce the duration of treatment exposure by prolonging time to prostate-specific antigen (PSA) recurrence without impacting eugonad state recovery. Methods: This phase II, randomised, open-label trial enrolled patients with rising PSA ≥ 0.2 ng/ml after radical prostatectomy and/or a PSA ≥ 1 following radiotherapy. Patients were randomised 1:1 to receive Abi (1 g PO daily) + P (5 mg PO daily) + ADT or ADT alone for 8 months. The primary end-point was PSA-free survival difference at 1 year following completion of therapy. Results: Between February 2013 and July 2016, 200 patients were enrolled. Of 100 patients randomised to each arm, 99 in the Abi +P arm and 98 in the ADT arm were evaluable. Median follow-up was 64.4 months. Median PSA-free survival was 27.0 months for the Abi +P-treated group versus 19.9 months for the ADT-treated group (hazard ratio [HR] 0.64, 95% confidence interval [CI] 0.47–0.87). The PSA-free survival at 1 year post-treatment completion was 98% for the Abi +P group and 88% for the ADT group. Median time to eugonad state was 13.1 months for the abiraterone-treated group and 12.8 months for the ADT-treated group. Median eugonad PSA-free survival was 12.5 months for the abiraterone-treated group versus 9.0 for the ADT-treated group (HR 0.72, 95% CI 0.53–0.98). There were no significant between-group differences in androgen deprivation-related adverse events. Conclusions: In men with biochemically recurrent prostate cancer following definitive treatment of the primary, finite duration treatment with ADT and Abi +P results in a significantly longer PSA relapse-free interval than treatment with ADT alone. Highlights: This trial investigated abiraterone in biochemically recurrent prostate cancer. All patients had castration-naïve disease. Abiraterone was added to ADT for 8 months. This led to a significantly increased PSA-free survival compared to ADT alone. The interval to subsequent systemic prostate cancer treatment was thus prolonged.